2011
DOI: 10.1063/1.3588033
|View full text |Cite
|
Sign up to set email alerts
|

Fast transient charging at the graphene/SiO2 interface causing hysteretic device characteristics

Abstract: Device instabilities of graphene metal-oxide-semiconductor field effect transistors such as hysteresis and Dirac point shifts have been attributed to charge trapping in the underlying substrate, especially in SiO2. In this letter, trapping time constants around 87 μs and 1.76 ms were identified using a short pulse current-voltage method. The values of two trapping time constants with reversible trapping behavior indicate that the hysteretic behaviors of graphene field effect transistors are due to neither char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 22 publications
5
109
1
Order By: Relevance
“…The graphene corrugations observed by a novel combined SEM/AFM/STM technique are suggested to be attributed to the partial conformation of the graphene to the SiO 2 , not to the intrinsic corrugations of graphene [316]. Besides, species like H 2 O may be trapped at the graphene/SiO 2 interface [317,318]. Water drainage between graphene and substrate also plays a significant role in the formation of wrinkles [319].…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…The graphene corrugations observed by a novel combined SEM/AFM/STM technique are suggested to be attributed to the partial conformation of the graphene to the SiO 2 , not to the intrinsic corrugations of graphene [316]. Besides, species like H 2 O may be trapped at the graphene/SiO 2 interface [317,318]. Water drainage between graphene and substrate also plays a significant role in the formation of wrinkles [319].…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…It was shown that the large hysteresis in the gate characterization curves of graphene FETs (GFETs) can be applied for memory device operation 23 . It was also demonstrated that this hysteresis arises due to trapped charge in the oxide dielectric layer 24 . However, the relatively slow dynamics and poor controllability of the trap density in these graphene memory devices require further improvement for realistic applications.…”
mentioning
confidence: 98%
“…However, several papers on hysteresis have reported time constants ranging from μsec to a few hundred seconds [14,26,27], indicating that many different physical mechanisms in addition to charge trapping are associated with the hysteretic I-V curves. The I-V curve shown in Fig.…”
Section: Hysteretic Device Characteristicsmentioning
confidence: 99%
“…With a limited understanding of the sources causing hysteresis, it is not easy to find a test method to measure intrinsic properties. Thus, conventional I-V measurements used for graphene devices showing hysteretic behaviors inherently include very significant errors [14].…”
Section: Device Structuresmentioning
confidence: 99%
See 1 more Smart Citation